IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS MUATAN LOKAL DI SMA MUHAMMADIYAH BRAJA SELEBAH TAHUN 2024 - wahulil jannah; Heri Cahyono; M. Ihsan Dacholfany (Universitas Muhammadiyah Metro, 2026)
SMA Muhammadiyah Braja Selebah has implemented an independent curriculum in the 2023/2024 academic year, especially in class X (ten). This independent curriculum provides opportunities for students to hone their talents and interests, focus on essential material, and develop character and competence. This research aims to determine the local content of the independent curriculum in Islamic religious education subjects, determine the implementation of the independent curriculum, and determine the factors inhibiting and supporting the implementation of the independent curriculum at SMA Muhammadiyah Braja Selebah Lampung. Apart from that, this research was conducted to explore in depth the uniqueness that exists at SMA Muhammadiyah Braja Selebah in implementing the independent curriculum in Islamic religious education subjects. This type of research is field research using a descriptive qualitative research method. Data collection techniques were carried out by means of observation, interviews, and documentation. The data analysis technique used is the concept of data analysis according to Miles and Huberman, namely, data collection, data reduction, data presentation, and drawing conclusions. According to the research results, researchers can conclude that the implementation of the independent curriculum at SMA Muhammadiyah Braja Selebah follows the stages in the independent curriculum, held P5 by implementing the activity of singing the song Indonesia Raya during the first break, then sing a song to you the country after the prayer will go home, Apart from that, to support the dimensions in P5, the school held the-111 th MILAD Muhammadiyah activity to implement the mutual cooperation dimension at Muhammadiyah Braja Selebah High School, apart from that, it has used the independent curriculum book. Then the local content of the independent curriculum in Islamic religious education subjects includes carrying out midday prayers, reciting the Koran, Friday prayers, women's studies, noon prayers, and kultum. The inhibiting factors are the lack of motivation for children to participate in the learning process, curriculum policies that do not fully use the independent curriculum, lack of learning media. Meanwhile, the supporting factors are children's motivation to learn, support from students' parents, adequate facilities and infrastructure, and teacher competence.